Impact of the US Food and Drug Administration registration of antiretroviral drugs on global access to HIV treatment - Chahal, Harinder Singh (BMJ Glob Health, 2018)
BACKGROUND: Since 2004, the US Food and Drug Administration’s (USFDA) dedicated drug review process in support of President’s Emergency Plan for AIDS Relief (PEPFAR) has made safe, effective and quality antiretrovirals (ARVs) available for millions of patients. Furthermore, the WHO and Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund) can add the USFDA-reviewed products to their respective formularies, through a novel process of ‘one-way reliance’. We assessed the number of ARVs made available through WHO and Global Fund based on the USFDA review. METHODS: We conducted a cross-sectional study of all the USFDA-reviewed PEPFAR drugs between 1 December 2014 and 20 March 2017 to determine 1) the percentage that are included on the WHO and Global Fund formularies; 2) the number of the USFDA ARVs supporting the WHO HIV treatment guidelines, and their uptake by WHO and Global Fund and 3) time between the USFDA review and WHO review of the same ARVs. FINDINGS: Overall, 91% (204/224) of the USFDA products appeared on either the WHO/Prequalification of Medicines Programme (PQP) or the Global Fund ARV lists. Forty-five per cent (100/224) and 83% (184/224) appear on WHO/PQP and Global Fund formularies through one-way reliance, respectively. Forty-one per cent (91/224) of the USFDA products support the WHO-preferred first-line HIV treatment options. Of these 91 products, 38% and 85% of products were adopted by WHO/PQP and Global Fund through one-way reliance, respectively. Sixty-six products that were fully reviewed and registered by WHO (vs one-way reliance) had also undergone the USFDA review; 46 of these were registered by WHO after the USFDA review was complete (median delay of 559 days (IQR 233–798 days)). CONCLUSIONS: The USFDA’s PEPFAR process is making safe and effective ARVs available worldwide, in part because the major global ARV procurement organisations rely on the USFDA registration as proof of quality. There is room for improved information sharing and collaboration to reduce duplication of effort, save resources and further expedite access to ARVs.